Dominica : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2006)
The Growth and Social Protection Strategy (GSPS) provides the framework for Dominica's economic and social policies over the next five years and sets out the macroeconomic framework; the growth strategy, including the enabling environment for private enterprise and sectoral strategies; and poverty reduction and social protection programs. Economic growth in Dominica was curtailed by a conjuncture of unfavorable developments, particularly with respect to trade, but there were underlying weaknesses in the economy such as a reliance on one or two sectors, with this lack of diversity exacerbating its vulnerability to economic shocks.